Challenges Kindergarten Administrators Face in Gaza City in Using E-learning in Light of Corona Pandemic - Aladam, Marwa Esam (Journal of Educational and Psychological Sciences, 2020)
The study aims to identify the challenges that kindergarten administrators face in Gaza city with using e-learning in light of the Coron pandemic. The study uses the descriptive and analytical approach, and the study covers all the kindergartens in Gaza city, which they are (350) managers. The researcher chose the kindergarten directors in the West Gaza District, which they are (132) managers as a sample for the study. The results showed that kindergarten administrators in Gaza city face difficulties in using e-learning in light of the Corona pandemic to a large extent, with an arithmetic average (1.92, and a relative weight (83.85%), and at the level of fields, the technical difficulties ranked first with an arithmetic average (4.23), With a relative weight (84.67%) and a very large degree, then administrative and financial challenges followed, and it's ranked second, with an arithmetic average (4.18), and a relative weight (83.65%) and to a large degree the difficulties related to the concept of e-learning ranked third, with an arithmetic average (4.161), with relative weight (83.23%), and to a large extent, The study illustrates the solutions to how to reduce these challenges, which they have educated the community about the importance of electronic education, the need to unify the educational platforms for children as a base, and train kindergarten administrators to use websites. The results did not reveal any statistically significant differences in the difficulties that kindergarten managers face in using E-learning refers to a variable of academic qualification, years of experience, or kindergarten type; The study recommended and illustrate the necessity to implement educational programs for kindergarten directors to train them on how to use an e-learning by using activating seminars and training programs for directorates to develop their electronic skills, and the necessity of conducting research studies in the field of e-learning in kindergartens in light of the current conditions.
Keywords: Kindergartens; Distance Education; Gaza city